Implementation of Biology Learning by Utilizing The Local Potential of The Citarum River to Increase Students' Environmental Literacy on Environmental Change Material - Intan Khairani; Saefudin Saefudin; Amprasto Amprasto (Postgraduate, University of Mataram, 2023)
This study aims to increase students' environmental literacy through the implementation of biology learning by utilizing the local potential of the Citarum River on environmental change material. The research method used is Quasi-experimental. The population in this study were all environmental literacy abilities of class X students of SMA Negeri 1 Baleendah, while the sample in this study was the environmental literacy of class X students of SMA Negeri 1 Baleendah which consisted of two classes as an experimental class and a control class totaling 88 people. The instruments used consisted of multiple choice questions for indicators of environmental literacy, knowledge and cognitive skills, and questionnaires for responsible attitudes and behavior indicators. The results showed that from the pretest and posttest scores there was an increase in scores on indicators of knowledge and cognitive skills seen from the average Ngain in the experimental class of 0.60 which could be categorized as medium and the control class was 0.45 which was categorized as medium. For indicators of responsible attitudes and behavior, the average Ngain score in the experimental class is 0.50, categorized as medium, and in the control class is 0.26, categorized as low. So it can be concluded that the implementation of biology learning by utilizing the local potential of the Citarum River can increase students' environmental literacy